High prevalence of Vitamin D deficiency among North Indian athletes - Ravi Gupta; Vaibhav Bohat; Anil Kapoor; Akash Singhal; Ashwani Soni; Gladson David Masih (Wolters Kluwer Medknow Publications, 2021)
Background: Vitamin D deficiency is high in athletes and has an impact on athletes' performance. Introduction: Assessment of serum Vitamin D levels in healthy North Indian sportspersons and its correlation with serum parathyroid hormone (PTH) levels and bone mineral density (BMD). Materials and Methods: Three-hundred and sixty-nine healthy athletes' aged 18-45 years were enrolled. Depending upon Vitamin D levels athletes were categorized into three groups: deficient (<20 ng/ml), insufficient (20-30 ng/ml), and sufficient (>30 ng/ml). BMD and serum PTH levels were assessed in all athletes and correlation was seen with Vitamin D levels. Results: Two-hundred and fifty-eight (69.9%) athletes were Vitamin D deficient, 51/369 (13.8%) were Vitamin D insufficient, and 60/369 (16.3%) athletes were Vitamin D sufficient. There was a direct correlation between low serum Vitamin D levels and low BMD (r = 0.473; P < 0.05). Overall, 114/369 (30%) athletes had low BMD and out of these 114 athletes, 108 (95%) were Vitamin D deficient. Serum PTH levels were found to have inverse relations with both Vitamin D (r= −0.629) and BMD (r=-0.267). Conclusions: Vitamin D deficiency is highly prevalent among the North Indian athletes and the presence of low Vitamin D (<20 ng/ml) levels is associated with low BMD and high PTH levels.